(untitled) (مجلة العلوم الشاملة, 2025)
This research investigates the impact of post-weld heat treatment (PWHT) on the mechanical properties of butt- welded low carbon steel joints. Welding processes can induce thermal stresses and microstructural changes that negatively affect mechanical performance. The study utilized Shielded Metal Arc Welding (SMAW) with controlled parameters and an E10-60 electrode. Non-destructive testing (NDT) methods, including Dye Penetrant Testing, UV Inspection, and Magnetic Field Detection, were applied to assess weld quality before and after welding. Subsequent heat treatment, specifically tempering at 550°C for 20 minutes followed by slow air cooling, was performed to balance hardness and toughness. Microstructural analysis and microhardness testing were conducted to evaluate the effects of the heat treatment on the welded joints. The results indicate that tempering significantly reduces hardness, particularly in the HeatAffected Zone (HAZ), and enhances toughness and ductility, which are crucial for preventing cracking and failure in welded joints.